2013
DOI: 10.1371/journal.pone.0067548
|View full text |Cite
|
Sign up to set email alerts
|

An Insight into the Changes in Human Plasma Proteome on Adaptation to Hypobaric Hypoxia

Abstract: Adaptation to hypobaric hypoxia is required by animals and human in several physiological and pathological situations. Hypobaric hypoxia is a pathophysiological condition triggering redox status disturbances of cell organization leading, via oxidative stress, to proteins, lipids, and DNA damage. Identifying the molecular variables playing key roles in this process would be of paramount importance to shed light on the mechanisms known to counteract the negative effects of oxygen lack. To obtain a molecular sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 93 publications
1
47
0
Order By: Relevance
“…Furthermore, the association found between lowest SaO 2 and serum vitamin D levels could suggest that hypoxia is a putative factor involved in vitamin D deficiency in patients with OSA, as reported in chronic obstructive pulmonary diseases. 23 However, considering that vitamin D binding-protein (VDBP) changes its serum level in response to chronic hypoxia, 24 further investigation of VDBP serum levels in patients with OSA before and after CPAP treatment would be necessary in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the association found between lowest SaO 2 and serum vitamin D levels could suggest that hypoxia is a putative factor involved in vitamin D deficiency in patients with OSA, as reported in chronic obstructive pulmonary diseases. 23 However, considering that vitamin D binding-protein (VDBP) changes its serum level in response to chronic hypoxia, 24 further investigation of VDBP serum levels in patients with OSA before and after CPAP treatment would be necessary in the future.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of LTH on PTH levels explains the synergistic interaction of LTH with pregnancy on increased levels of bioactive vitamin D. Finally, our study revealed that this ovine LTH model is unique in showing LTH decreases in renal CYP24a1. Previous in vitro studies have shown that hypoxia upregulates the expression of CYP27b1, CYP24a1, and VDBP gene expression in human cells (1,27). The effect of hypobaric hypoxia on VDR-related gene expression is thought to be indirect, as there are no consensus hypoxia-inducible factor-1␣ DNA-binding elements in these genes (8,19).…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, given that vitamin D binding protein (VDBP) changes its serum level in response to chronic hypoxia, further investigation is warranted to better understand this relationship [70]. …”
Section: Osas and Vitamin D Insufficiencymentioning
confidence: 99%